Tracing Bank Storage and Hyporheic Exchange Dynamics Using 222Rn: Virtual and Field Tests and Comparison With Other Tracers. Issue 5 (6th May 2021) - Liao, Fu; Cardenas, M. Bayani; Ferencz, Stephen B.; Chen, Xiaobing; Wang, Guangcai
Abstract: Dynamic hydrologic exchange flows in river beds and banks are important for many ecosystem functions throughout river corridors. Here we test whether the exchanges and the associated mixing between a flooding river and groundwater within the river's bank can be effectively traced by Radon‐222 ( 222 Rn), a naturally occurring, inert, radiogenic, and radioactive gas that can be analyzed and monitored in situ. The assessment was done by simulation of groundwater flow and reactive transport of 222 Rn in the bank following a single, relatively rapid (hours long) flood wave and auxiliary field observations of 222 Rn, temperature and total dissolved solids (a surrogate for any ionic conservative tracer). Results illustrate that 222 Rn is more effective than temperature and total dissolved solids in tracing dynamic hyporheic exchange. 222 Rn variations in space and time are larger than the analytical uncertainty of common measurement methods. The individual effects of aquifer hydraulic conductivity, dispersivity, river water 222 Rn concentration, and bank topography were analyzed through sensitivity analysis. Larger hydraulic conductivity and dispersivity, lower 222 Rn concentration in river water relative to groundwater, and gentler bank slopes resulted in a more prominent and traceable 222 Rn signal. The transport and residence time of exchanged water may be estimated and interpreted using reactive transport models such as those implemented here. However, such application is sensitive to fluctuations in river water 222 Rn, requiring it to be well characterized. The assessment provides guidance for using 222 Rn as a tracer for groundwater and surface water interactions in dynamic settings. Key Points: The Radon‐222 ( 222 Rn) can be an effective tracer for rapid dynamic subsurface exchange flows and mixing within a few meters inside river banks The 222 Rn is a more effective tracer than temperature and conservative solutes under certain situations The quantitative analysis of 222 Rn within the banks close to the river is sensitive to fluctuations in river water 222 Rn